2000
DOI: 10.1046/j.1365-2672.2000.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that water transmits the disease caused by the fish pathogen Photobacterium damselae subsp. damselae

Abstract: The transmission through water of the disease caused by the fish pathogen, Photobacterium damselae subsp. damselae, as well as the role of the skin mucus in the initial steps of the infection, have been studied. All tested strains resisted the bactericidal activity of the mucus and showed an ability to adhere to it, but only those virulent by the intraperitoneal route were infective through water. Moribund fishes showed the typical signs of the disease: haemorrhaged areas on the body surface and ulcerative les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 19 publications
4
46
0
2
Order By: Relevance
“…piscicida strains showed a unique API 20E profile, 2 005 004. All PCR reactions yielded definite amplicons of 267-bp fragment and the sequences of 16S RNA were 100% homogenous with The severity and frequency of photobacteriosis infections boost at high water temperatures similar to conditions noticed in the investigated farm, 25°C, inducing fatal outbreaks in fish ultimately at water temperatures around 22°C [35]. There is also a significant seasonal variation in lice infestations with peak prevalence and intensity values during summer season [50,51].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…piscicida strains showed a unique API 20E profile, 2 005 004. All PCR reactions yielded definite amplicons of 267-bp fragment and the sequences of 16S RNA were 100% homogenous with The severity and frequency of photobacteriosis infections boost at high water temperatures similar to conditions noticed in the investigated farm, 25°C, inducing fatal outbreaks in fish ultimately at water temperatures around 22°C [35]. There is also a significant seasonal variation in lice infestations with peak prevalence and intensity values during summer season [50,51].…”
Section: Discussionsupporting
confidence: 54%
“…Sea lice irritate and injury fish skin by their rasping piston-like mouthparts hence increase mucus secretions thereby provide a rich source of glycoproteins which is critical for bacterial adhesions, a significant step in the pathway of infectious diseases affecting fish [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Snoussi et al [265] confirmed that V. alginolyticus strains isolated from a bathing and fishing area (Khenis, Centre of Tunisia) show a specific binding capability to gilthead sea bass and gilthead sea bream mucus. Fouz et al [281] noted that Photobacterium damselae subsp. damselae strains showed a strong ability to adhere to the fish skin mucus from eel and turbot, exhibiting a degree of adhesion similar to that previously reported for other fish pathogens (V. vulnificus, V. alginolyticus, V. anguillarum, Aeromonas hydrophila, P. damselae subsp.…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%
“…The primary route for introduction of pathogens to a farm is through transport of infected seedlings from hatcheries (Piper et al 1982), food, infected equipment, staff and vessels (e.g. Kennedy & Fitch 1990, Ruiz et al 2000, Murray & Peeler 2005, as well as through water currents (Fouz et al 2000, Amundrud & Murray 2009, Frazer 2009, Salama & Murray 2011. Monitoring of animal health, biosecurity programmes and other disease control measures, including disease management areas or surveillance zones around farms in site selection programmes, are designed to minimize the risk of spreading disease through these pathways (DAFF 2000, Scottish Executive 2000, Rae 2002, Subasinghe et al 2004, Bondad-Reantaso & Subasinghe 2008, Lyngstad et al 2008, Mardones et al 2009, Marine Scotland 2010.…”
Section: Introductionmentioning
confidence: 99%